1997
DOI: 10.1007/s001250050786
|View full text |Cite
|
Sign up to set email alerts
|

CD8 cytotoxic T-cell clone rapidly transfers autoimmune diabetes in very young NOD and MHC class I-compatible scid mice

Abstract: Nonobese diabetic (NOD) mice spontaneously develop an autoimmune diabetes resembling human insulin-dependent diabetes mellitus (IDDM). Several lines of evidence suggest that T cells are responsible for mononuclear cell infiltration into the islets (insulitis) and destruction of beta cells in NOD mice. Disease transfer studies have shown that both splenic CD4 and CD8 T cells from diabetic NOD mice are necessary to transfer diabetes to newborn or sublethally irradiated NOD mice [1, 2] and islet-specific CD4 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 27 publications
2
9
0
Order By: Relevance
“…As we and others have previously reported, CD8 ϩ effector T-cells induce overt diabetes without the help of CD4 ϩ T-cells (17,21). These results indicated that Fas/FasLmediated cytolysis was not responsible for the CD8 ϩ T-cell-mediated ␤-cell destruction.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…As we and others have previously reported, CD8 ϩ effector T-cells induce overt diabetes without the help of CD4 ϩ T-cells (17,21). These results indicated that Fas/FasLmediated cytolysis was not responsible for the CD8 ϩ T-cell-mediated ␤-cell destruction.…”
Section: Discussionsupporting
confidence: 69%
“…ϩ T-cells (CD8 ϩ CTL [cytotoxic T lymphocytes]) were generated from lymphocytes infiltrating islets in 20-week-old female NOD mice (17). Isolated islets containing infiltrating lymphocytes were cultured in RPMI 1640 medium supplemented with 10% FCS and 3 U/ml recombinant interleukin-2 (rIL-2) (Takeda Pharmaceutical, Osaka, Japan) in a humidified incubator at 37°C.…”
Section: Cells Islet-derived Cd8mentioning
confidence: 99%
See 1 more Smart Citation
“…Activated CD8-positive CTLs play a rate-limiting role in the onset and early progression of insulin-dependent diabetes mellitus (IDDM) by targeting and destroying the insulin-producing β-islet cells of the pancreas [1][2][3][4][5][6] . In addition to their role in autoimmunity, activated CTLs are known to aid in the rejection processes associated with solid organ transplantation 7 and in Graft versus Host Disease 8 .…”
Section: Research Articlesmentioning
confidence: 99%
“…Based on evidence from homing of CD8 ϩ T cell clones to the lung (11), islets of Langerhans (12), internal elastic lamina and lamina propria of the gut (13), and other inflamed tissues, it is clear that lymphocyte activation is required for recruitment of effector T cells. The sequence of events required is thought to encompass rolling, activation, arrest, and transmigration, akin to the paradigm known for neutrophil recruitment (10).…”
mentioning
confidence: 99%